TEST DIAGNOSIS AND NOISE REDUCTION RECTIFICATION OF ACCELERATING VEHICLE INTERIOR BOOMING NOISE OF A PASSENGER CAR - LIU Gang; WANG ShengBo; ZANG ZeNan; YANG Yi (Jixie qiangdu)
Based on the generation mechanism and transmission path of the roar, this paper expounds the corresponding control strategies for the roar of different paths. Aiming at the roaring noise in the accelerating car of a passenger car, the corresponding troubleshooting methods for different paths when the roaring sound is diagnosed based on the transmission path are introduced; and after determining that the problem comes from the structural transmission path of the intake system, further analysis: There is a mode with a corresponding frequency at the intercooler bracket, so the engine excitation is amplified here, and coupled with the body acoustic cavity mode, and finally forms the roar of the car; furthermore, it is clear that the intercooler installation bracket structure and the The optimized plan for cooling vibration isolation is to improve the mode of the intercooler support, improve the vibration isolation effect, reduce energy transfer, eliminate modal coupling, and solve the problem. This article has certain reference value for the roar control of passenger cars.